2023
DOI: 10.1093/femsre/fuad014
|View full text |Cite
|
Sign up to set email alerts
|

Ruminococcus gnavus: friend or foe for human health

Abstract: Ruminococcus gnavus was first identified in 1974 as a strict anaerobe in the gut of healthy individuals, and for several decades, its study has been limited to specific enzymes or bacteriocins. With the advent of metagenomics, R. gnavus has been associated both positively and negatively with an increasing number of intestinal and extra-intestinal diseases from inflammatory bowel diseases to neurological disorders. This prompted renewed interest in understanding the adaptation mechanisms of R. gnavus to the gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 206 publications
0
26
1
Order By: Relevance
“…These taxa have previously been identified to be associated with IBD (Hassouneh et al, 2021; Pisani et al, n.d.). R. gnavus has been extensively reported to be associated with multiple intestinal and extra-intestinal disorders (Crost et al, 2023) and was shown to actively promote inflammation through TLR4 dependent TNF-alpha secretion in response to the polysaccharide glucorhamnan (Henke et al, 2019). F. plautii and C. symbiosum were implicated in bloodstream infections (Elsayed & Zhang, 2004; Karpat et al, 2021), and Bacteroides fragilis is known to be an opportunistic pathogen (Wexler, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These taxa have previously been identified to be associated with IBD (Hassouneh et al, 2021; Pisani et al, n.d.). R. gnavus has been extensively reported to be associated with multiple intestinal and extra-intestinal disorders (Crost et al, 2023) and was shown to actively promote inflammation through TLR4 dependent TNF-alpha secretion in response to the polysaccharide glucorhamnan (Henke et al, 2019). F. plautii and C. symbiosum were implicated in bloodstream infections (Elsayed & Zhang, 2004; Karpat et al, 2021), and Bacteroides fragilis is known to be an opportunistic pathogen (Wexler, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] The mechanisms of gut microbiota-mediated modulation of T2D risk, including the role of Ruminococcus gnavus and its association with several features of metabolic syndrome and development of T2D, have been reviewed in detail. 12 R gnavus was robustly associated with an increase in fat mass, waist circumference, serum triglycerides, C-reactive protein, HbA1c (hemoglobin A1c), and a decrease in HDL (highdensity lipoprotein), based on stratified analyses of a large Norwegian cohort using a validated quantitative polymerase chain reaction method. An investigation on long-term associations between gut microbiome composition and incident T2D identified R gnavus as 1 of the 4 species consistently associated with incident T2D.…”
Section: See Accompanying Article On Page 477mentioning
confidence: 99%
“… R. gnavus end-fermentation products of carbohydrates include acetate, formate and ethanol, as well as propanol and propionate but not butyrate [3].…”
Section: Taxonomy and Propertiesmentioning
confidence: 99%
“…gnavus to elicit anti- or pro-inflammatory responses is reflected in a mouse model of diseases showing a beneficial or detrimental outcome of R. gnavus supplementation (as reviewed in [3]). At the molecular level, some R.…”
Section: Key Features and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation